THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND THE LEVEL OF MEDICATION ADHERENCE IN TYPE 2 DIABETES MELLITUS PATIENTS AT KARUNIA KASIH HOSPITAL - De Sousa, Alexandra Delfino Pires; Aminah, Siti (HEARTY, 2025)
Background: Diabetes mellitus is a medical condition or chronic metabolic disorder that has various causes and is characterized by elevated levels of blood sugar, accompanied by disturbances in the metabolism of carbohydrates, lipids, and proteins due to insufficient insulin function (Diyah Chandra et al., 2021). Type 2 diabetes is a term used to describe a condition in which hyperglycemia occurs despite the presence of sufficient insulin (Sulastri, 2021). According to the International Diabetes Federation (IDF, 2021), Indonesia ranks seventh in the world, following China, India, the United States, Pakistan, Brazil, and Mexico, with a total of 10.7 million diabetes patients aged between 20 and 79 years. The Indonesian Ministry of Health (2020) reported that Indonesia ranks seventh among the top 10 countries with a total of 10.7 million individuals suffering from diabetes mellitus, and additionally, 1.5 million people have died from diabetes mellitus. In 2015, there were approximately 39.5 million cases of diabetes, resulting in 56.4 million deaths worldwide. According to the outcomes of the 2018 Basic Health Research (Riskesdas), familial support constitutes a reciprocal interaction among family members, involving the provision of assistance to those within the family who require it. The assistance offered encompasses informational, emotional, and instrumental support (Kamaryati & Malathum, 2020). Compliance represents an individual’s adherence to the treatment regimen they need to follow in their daily life. Several terms are associated with medication adherence, including the concepts of compliance and adherence. The concept of compliance indicates the extent to which a patient follows the advice provided by medical experts. Conversely, the concept of adherence refers to the behavior of taking medication in accordance with the agreement established between the patient and the prescriber (Selly, 2020, as cited in Pradana, 2021). Objective: The objective of this research was to examine the association between family support and the degree of medication adherence in patients with type 2 diabetes mellitus at Karunia Kasih Hospital. Methods: The research design employed in this research is analytical-descriptive, which involves examining the relationship between independent and dependent variables. The data were collected through a questionnaire completed by respondents who are patients with type 2 diabetes mellitus. The statistical test results yielded a p-value of 0.000. Therefore, it can be concluded that there is a significant relationship between family support and medication adherence among patients with type 2 diabetes mellitus at Karunia Kasih Hospital.